Evidence for low-temperature antiferromagnetic phase transition in Ising singlet magnet KTb(WO4)2 - Khatsko, E.; Paulsen, C.; Rykova, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The magnetic susceptibility and magnetization measured along the b axis of a KTb(WO4)2 single crystal was investigatedexperimentally in the temperature range 70 mK–6 K and in magnetic fields up to 8 T. The results allow us to make conclusion that singlet magnet KTb(WO4)2 undergoes an antiferromagnetic phase transition Tc = 0.65 K.